The efficacy and safety of adamgammadex for reversing rocuronium-induced deep neuromuscular blockage. A systematic review and network meta-analysis (Journal of Medical Science, 2025)
Aim. We aim to evaluate the efficacy and safety of adamgammadex, a new modified γ-cyclodextrin, in reversing rocuronium-induced neuromuscular blockade compared with sugammadex or placebo. Material and methods. We comprehensively searched three electronic databases (PubMed, Scopus, and ScienceDirect) from inception until February 2024 to detect all randomised controlled trials comparing adamgammadex versus sugammadex or placebo. STATA software 17 and RevMan version 5.4 were used for network and pairwise meta-analyses, respectively. The study protocol was prospectively registered in PROSPERO (CRD42024516623). Results. Five randomised controlled trials comprising 530 patients were included in our study. There was a statistically significant difference between adamgammadex and sugammadex compared to placebo in the recovery time of neuromuscular function. A dose-response relationship was observed except for adamgammadex 7 mg/kg, which ranked first. Sugammadex was found to be more effective than a similar dose of adamgammadex. There was a non-significant difference between adamgammadex and sugammadex compared to placebo in the incidence of adverse events. Conclusions. Adamgammadex or sugammadex can be a safe and effective therapeutic option in reversing rocuronium-induced neuromuscular blockade. More clinical trials with larger sample sizes should be conducted to obtain better evidence regarding these two drugs’ most effective and safe doses.